An electrophysiological investigation of skeletal muscle in human chronic Chagas' disease - Olga P. Sanz; A. F. Ratusnu; G. G. Aristimuño; E. M. O'Neill; R. E. P. Sica (Arquivos de Neuro-Psiquiatria)
An electrophysiological study has been made of the thenar, hypothenar, soleus and extensor digitorum brevis muscles and their inervation in 90 patients with chronic Chagas' disease. Some of them showed a reduced number of functional motor units with increased size of many of the surviving units. No decremental muscle response was found to repetitive nerve stimulation. Motor and sensory conduction velocities as well as motor terminal latencies were on the normal range. These findings suggested that the muscle changes resulted from a primary defect of the alpha spinal motoneurone soma.